Analyzing rice industry in Malaysia: 1976 – 2005 / Mohammad Faiz Ikhlas - Ikhlas, Mohammad Faiz (Faculty of Business and Management, 2008)
The primary objective of this paper is to analyze rice industry in Malaysia. Since we are facing food crisis, it is good to understand our Government's policy towards food and agriculture products. The paper reviews research on the analysis of rice production, average yield per hectare and areas planted in Malaysian agriculture sector. Data from year 1976 until 2005 were chosen to differentiate the impact of agriculture development phase. Discussions then focus on how the National Agricultural Policy 1, 2 and 3 can affect the production of paddy and its contribution. After made a series of analysis, we found that Government incentives, policies and subsidies have a significant impact towards agriculture sector. Year 1984 and 1985 were the turning point for such industry to boost in Malaysian economy.